1965
DOI: 10.1037/h0022217
|View full text |Cite
|
Sign up to set email alerts
|

Mental activity at sleep onset.

Abstract: Experimental data, based upon a total of 212 hypnagogic awakenings contributed by 9 Ss, are presented on the incidence of reports of various forms of hypnagogic mentation and on the relationship of such reports to EEG activity. It was found that mental activity in some form or another was invariably reported throughout the hypnagogic period. Content reported was predominantly visual and lacking in affective intensity and it became increasingly hallucinatory and unamenable to voluntary control as EEG patterns s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
173
2
4

Year Published

1966
1966
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(197 citation statements)
references
References 17 publications
(13 reference statements)
18
173
2
4
Order By: Relevance
“…Emotional intensity was low from the start and evinced little difference at any of the awakening junctures. These findings are consistent with previous studies that revealed significant change in sensory and thought process during sleep onset, while emotional experiences maintained a low intensity throughout (e.g., Foulkes & Vogel, 1965;Gibson et al, 1982;Hori, Hayashi, & Hibino, 1992;Hori, Hayashi, & Morikawa, 1991). This study's most significant finding is that control over the thinking process is the most prominent subjective experience that is associated with the judgment of having fallen asleep.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Emotional intensity was low from the start and evinced little difference at any of the awakening junctures. These findings are consistent with previous studies that revealed significant change in sensory and thought process during sleep onset, while emotional experiences maintained a low intensity throughout (e.g., Foulkes & Vogel, 1965;Gibson et al, 1982;Hori, Hayashi, & Hibino, 1992;Hori, Hayashi, & Morikawa, 1991). This study's most significant finding is that control over the thinking process is the most prominent subjective experience that is associated with the judgment of having fallen asleep.…”
Section: Discussionsupporting
confidence: 92%
“…Behavioral indicators of sleep onset include: a decrease in sensory threshold, a cessation of responses to external stimuli (e.g., Anliker, 1966;Ogilvie & Simons, 1992;Ogilvie, Simons, Kuderian, MacDonald, & Rustenburg, 1991;Ogilvie & Wilkinson, 1984, 1988Ogilvie, Wilkinson, & Allison, 1989;Simon & Emmons, 1956), and a decrease in muscle strength (e.g., Jacobson, Kales, Lehmann, & Hoedemaker, 1964;Litchman, 1974) were also observed in the course of the sleep onset process. And, as regards the subjective experience of sleep onset, loss of awareness of environmen-tal stimuli and the loss of control over thought processes have both been reported (e.g., Foulkes & Vogel, 1965;Gibson, Perry, Redington, & Kamiya, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, self-reports of sleep may be altered in clinical situations: insomniacs were more likely to report themselves as awake when actually awoken from stage 2 sleep than controls (Moore et al, 1981). In terms of subjective experiences, arousals during this sleep onset period can produce self-reports of sensory experiences that would appear to represent dreaming (Foulkes and Vogel, 1965;Hori, 1994).…”
Section: Subjective Measuresmentioning
confidence: 99%
“…A continuity has also been established between immediate pre-sleep, and sleep onset mentation that was to a certain extent co-existent with waking fantasy, as determined by the T.A.T. (Foulkes and Vogel, 1965;Vogel et al, 1966;Foulkes 1966;Vogel et al, 1972). Wood (1962) found that social isolation for a period of one day affected the content of his subjects' dreams recorded that night.…”
Section: Day Residuementioning
confidence: 99%